Multinationals and Exports in a Large and Protected Developing Country - Cinquetti, Carlos A. [UNESP] (Wiley-Blackwell, 2008)
This paper examines an industry-level model developed to analyze the impact of affiliates of multinational firms (MNFs) on the host country's revealed comparative advantages (RCAs), which predicts that the referred impact is given by both technology service and industry orientation. Based on Brazilian manufacturing industries during the import-substitution industrialization, panel data estimates show that MNFs negatively affected RCA, which is explained by location advantages in industries presenting comparative disadvantages, as reinforced by a location model. Two other important results are: (i) import protection had a stronger anti-export effect on multinationals than on national firms; (ii) MNFs were concentrated in industries with lower world-export growth.